Impact exercises for offensive and defensive skills of using mirrors in the level of satisfaction with the development of motor - qahtan, Israa (Journal of Physical Education, 2010)
The ressarch aim is prepare for training for offensive & defensive movements by using the mirroes in developing the level of the motional contentednss of female students of joust & knowing differences between the two groups the experimental & the controller by the effect of the offensive & defensive movements by using the mirrors in developing the motional contentednss level of female students of joust, the ressarcher used the experimental methodizing over the research sample of third grade students of the physical education college for girls, and their cound has reached to 36 students, and the researcher came over with several conclusions which they are: 1- The used training were helpful for developing the motional contentedness level for the research sample. 2- The existenece of incorporeal differences in the level of the motional contentedness in the two tests the before & the after for the controller group which was for the benefit of the after test. 3- The existence of incorporeal differences in the level of the motional contentedness in the two tests the before & the after for the experimental group which was for the benefit of the after test And the researcher has come out with several recommendations which they are ; 1- Developing on training treining that prepared by the researcher for all levels of students& players. 2 Making the same trainings that used for the experimental group on the controller group for not diverging in the students levels